2017
DOI: 10.1111/jbi.13114
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene climatic fluctuations drive isolation and secondary contact in the red diamond rattlesnake (Crotalus ruber) in Baja California

Abstract: Aim: Many studies have investigated the phylogeographic history of species on the Baja California Peninsula, and they often show one or more genetic breaks that are spatially concordant among many taxa. These phylogeographic breaks are commonly attributed to vicariance as a result of geological or climatic changes, followed by secondary contact when barriers are no longer present. We use restriction-site associated DNA sequence data and a phylogeographic model selection approach to explicitly test the secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…In these models, we fixed the topology of the four populations based on the results from SNAPP and we fixed the initial divergence time within this group and the divergence between P. emoryi and P. slowinskii at 2.97 mya and 590 kya, respectively (Chen, Lemmon, Lemmon, Pyron, & Burbrink, ). These models also allowed for recent gene flow between adjacent populations and we used a mutation rate of 7.26 × 10 –9 (Harrington, Hollingsworth, Higham, & Reeder, ) assuming a 3‐year generation time (estimate for P. emoryi ; Ernst & Ernst, ). The two‐population models differ only in the parameterization of gene flow between the ancestral lineages (see Figure a), such that these models are simplifications of isolation with migration (Figure a—IM) or, alternatively, in strict allopatry across the Mississippi River (Figure a—ISO).…”
Section: Methodsmentioning
confidence: 99%
“…In these models, we fixed the topology of the four populations based on the results from SNAPP and we fixed the initial divergence time within this group and the divergence between P. emoryi and P. slowinskii at 2.97 mya and 590 kya, respectively (Chen, Lemmon, Lemmon, Pyron, & Burbrink, ). These models also allowed for recent gene flow between adjacent populations and we used a mutation rate of 7.26 × 10 –9 (Harrington, Hollingsworth, Higham, & Reeder, ) assuming a 3‐year generation time (estimate for P. emoryi ; Ernst & Ernst, ). The two‐population models differ only in the parameterization of gene flow between the ancestral lineages (see Figure a), such that these models are simplifications of isolation with migration (Figure a—IM) or, alternatively, in strict allopatry across the Mississippi River (Figure a—ISO).…”
Section: Methodsmentioning
confidence: 99%
“…However, the phylogeographic breaks are not all consistent. For example, Harrington et al (2018) found a different genetic division in a rattlesnake, Crotalus ruber, centered south of the Vizcaino Desert and they concluded there was secondary contact with northward gene flow. These patterns also contrast with other species, such as the California gnatcatcher (Polioptila californica), which prior data have shown shows no apparent divisions across Baja (Zink et al 2000(Zink et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The central‐margin hypothesis puts forward qualitatively similar predictions where the highest genetic variation is expected to be harboured at the core of the species range, decreasing from the core towards the range margin (Brown, ; Eckert et al, ; Guo, ). Furthermore, at secondary contact zones between previously isolated lineages there is room for both neutral and adaptive gene flow (Carvalho et al, ; Harrington, Hollingsworth, Higham, & Reeder, ; Linnen, Kingsley, Jensen, & Hoekstra, ), which may lead to a nonlinear relationship between genetic variation and latitude.…”
Section: Introductionmentioning
confidence: 99%